Linguistic Perspectives on Nominating Human Names - Thao, Nguyen Van; Trang, Trinh Thu; Herman (International Journal of Psychosocial Rehabilitation, 2020)
This article aims at investigating the nomination of human names through an empirical survey deployed at kindergarten, primary and secondary schools in a selective commune of a province in Vietnam. The data is collected and classified in reference to various educational levels of the national education system. By collecting the primary data related to the nominated names of all the students enrolled in the schools, we employed semantic analysis and comparison methods to analyze and compare the nominating structures, specifically surname, middle name and given name. The data of full names was then separated into groups on the basis of the implied meanings for further investigation. The names containing 4- syllable structures have a direct link with the parents’ desire for their children. The meanings of many names are apparently found in flowers, plants, rivers, mountains, communes in districts, asteroids, meteorological phenomena. Another type of nominating proper name that is inherently traditional but also very exclusive is to express happiness, luck in business , hospitality and human morality. The research, therefore, can provide a deeper insight about linguistically critical perspectives of the Vietnamese in nominating things in general and human proper names in particular.